1997
DOI: 10.1084/jem.185.9.1605
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Early and Early Lytic Cycle Proteins Are Frequent Targets of the Epstein-Barr Virus–induced Cytotoxic T Cell Response

Abstract: Epstein-Barr virus (EBV), a human γ-herpesvirus, can establish both nonproductive (latent) and productive (lytic) infections. Although the CD8+ cytotoxic T lymphocyte (CTL) response to latently infected cells is well characterized, very little is known about T cell controls over lytic infection; this imbalance in our understanding belies the importance of virus-replicative lesions in several aspects of EBV disease pathogenesis. The present work shows that the primary CD8+ CTL response to EBV in infectious mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
254
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(269 citation statements)
references
References 53 publications
14
254
1
Order By: Relevance
“…In fact, whereas similar high frequencies of T cells reactive to the BMLF-1 (GLC) epitope were obtained using IFN-DCs or IL-4-DCs as stimulators, the expansion of T cells specific for the gp350 epitope was promoted exclusively by IFNDCs. Several studies have demonstrated that responses to lytic cycle Ags, including BMLF-1, are detectable in CTL memory (21,30,31) and can dominate those to latent cycle Ags (32), as in the case of donor LL, whose basal frequency of T cells reactive against the BMLF-1 (GLC) epitope largely exceeded that of each latent cycle Ag reactivity tested. Moreover, BMLF-1 (GLC) epitope-specific T cells can be easily detected in sensitive ELISPOT assays by adding the corresponding peptide to total PBMCs as responders (30,32), indicating that relatively inefficient APCs, such as the IL-4-DCs used in this study, can stimulate T cells reactive to this immunodominant epitope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, whereas similar high frequencies of T cells reactive to the BMLF-1 (GLC) epitope were obtained using IFN-DCs or IL-4-DCs as stimulators, the expansion of T cells specific for the gp350 epitope was promoted exclusively by IFNDCs. Several studies have demonstrated that responses to lytic cycle Ags, including BMLF-1, are detectable in CTL memory (21,30,31) and can dominate those to latent cycle Ags (32), as in the case of donor LL, whose basal frequency of T cells reactive against the BMLF-1 (GLC) epitope largely exceeded that of each latent cycle Ag reactivity tested. Moreover, BMLF-1 (GLC) epitope-specific T cells can be easily detected in sensitive ELISPOT assays by adding the corresponding peptide to total PBMCs as responders (30,32), indicating that relatively inefficient APCs, such as the IL-4-DCs used in this study, can stimulate T cells reactive to this immunodominant epitope.…”
Section: Discussionmentioning
confidence: 99%
“…ANOVA test paired with Tukey-Kramer comparison was used for calculating the significance of the differences in the survival times of mice. Table I reports the HLA typing of the three healthy EBV-seropositive donors and the sequence of the EBV peptides, known to be CTL epitopes (15)(16)(17)(18)(19)(20)(21)(22)(23), used in this study. In all the experiments described in this work, the DC preparations were generated from immunomagnetically purified CD14 ϩ monocytes by 3-day culture in GM-CSF and IFN (IFN-DCs) or IL-4 (IL-4-DCs).…”
Section: Human (Hu)-pbl-scid Mouse Modelmentioning
confidence: 99%
“…Peptides synthesized by FMOC chemistry were: melan-A, ELAGIGILTV, a variant of the 26 -35 epitope, which binds better to HLA-A2 than the natural peptide due to an altered anchor residue, but which is recognized by the same CTL as the natural peptide (26); influenza, GILGFVFTL, the influenza matrix protein 58 -66 epitope (27); EBV, GLCTLVAML, the 280 -288 epitope from the lytic protein BMLF1 of EBV (28,29).…”
Section: Peptides and Tetramersmentioning
confidence: 99%
“…Expression libraries of tumor cDNAs showed that the target of these CTL was melan-A, a lineage-specific molecule also expressed on normal melanocytes (2,3). The dominant HLA-A2-restricted epitope of melan-A originally appeared to be melan-A [27][28][29][30][31][32][33][34][35] (AAGIGILTV) (4), but subsequent experiments showed melan-A 26 -35 (EAAGIGILTV) is also recognized by CTL, and binds better to HLA-A2 (5). Many laboratories have since found it relatively easy to generate CTL specific for this epitope from HLA-A2 ϩ melanoma patients (6,7), and it therefore seemed that melan-A 26/7-35 might be the most commonly recognized epitope among all the known targets of melanoma Ag-specific CTL (6).…”
mentioning
confidence: 99%
“…Although the mechanisms have not been clearly established (reviewed in Refs. 4,5), the limited pattern of epitopes recognized among the large number of potent immunogenic epitopes encoded by viruses (immunodominant epitopes) is an important factor for the limitation of the TCR repertoire diversity (6)(7)(8)(9). Furthermore, in several situations, certain virus epitopes recruited a low number of clonotypes (reviewed in Ref.…”
mentioning
confidence: 99%